Thomas Revisited: A Rejoinder to Denzey Lewis, Kloppenborg and Patterson - Gathercole, Simon J. (Journal for the study of the New Testament, 2014)
This article makes some observations on the Gospel of Thomas in connection with the responses to Goodacre’s Thomas and the Gospels and Gathercole’s Composition of the Gospel of Thomas. It notes that the order of Thomas’s sayings and the genre of Thomas are irrelevant to the question of dependence or independence. More important to the question is the unity of Thomas, which is stronger than is often thought, though Thomas clearly is inﬂuenced by a number of (known and unknown) sources. The means of the inﬂuence of the Synoptic Gospels remains unknown. These arguments are strengthened by attention to aspects of Gos. Thom. 33 and Gos. Thom. 65–66. Overall, there are no obstacles to concluding that Thomas was inﬂuenced by the Synoptic Gospels.